(untitled) (Bangladesh Journal of Agricultural Research, 2015)
Flower morphology and bud development of pummelo accessions CG-1, CG-18 and CG-151 were studied at the Pummelo Orchard of Regional Agricultural Research Station, BARI, Akbarpur, Moulvibazar and the Horticulture Laboratory of Bangabandhu Sheikh Mujibur Rahman Agricultural University during 2008-2009. Pummelo flowers were bisexual, bore singly on leaf axils or in clusters with or without leaf on stem in all accessions, and colour were white. Calyx diameter varied from 0.94 in CG-1 to 1.02 in CG-18. Number of petals per flower ranged from 4.0 to 4.5. Anthers were yellow in colour and only CG- 151 produced few rudimentary styles. Diameter of stigma varied from 0.39 mm to 0.49 mm. Number of locules per ovary was in between 14.6 to16.0 and number of ovules per locules varied from 4.0 to 9.0. Stages of floral bud development from initiation to anthesis were divided into 9 distinct stages. In pummelo, a total of 27.7 to 31.2 days were required from a bud initiation to reach its fully developed stage. Suitable time for emasculation of pummelo flowers was found within 26 days from flower bud initiation. Between 3:00am to 5:00am, about 76% flowers were found to be opened and between 4:00pm to 5:00pm in all the three accessions, dehiscence of pollens was recorded. Abscission of stamen, petal and style started after 50.8, 76.4 and 162.3 hrs and completed after 128.4, 137.9 and 228.3 hrs of anthesis, respectively. Bangladesh J. Agril. Res. 40(2): 177-188, June 2015